Off-pump open repair of false aneurysm of aortic isthmus: This technique is still relevant - Adama Sawadogo (Indian Journal of Vascular and Endovascular Surgery, 2021)
Pseudoaneurysm is a rare long-term complication following coarctation of aorta repair. Thoracic endovascular aortic repair is the most common approach. However, under some circumstances, this cannot be performed. Therefore, the traditional open approach is indicated. Although the potential ischemia of spinal cord is related to this approach, it remains an efficient alternative. The authors report a case of late pseudoaneurysm of the distal aortic arch following coarctation of aorta repair in a 26-year-old male that has been successfully repaired by left thoracotomy.